Primary Slangs Occurred on Greyson Chance’s Selected Songs - I Dewa Ayu Devi Maharani Santika; Komang Dian Puspita Chandra; Purnamasari, Ni Wayan Vera (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
Many slang words are become the part of people's utterances nowadays. It is also often used on song lyrics. This study aimed to analyse the slang words that occur on the selected song of Greyson Chance's, specifically for the primary type of slang words which is proposed by Chapman (2007: 8). The process of creating slang is also analysed based on the theory proposed by Yule (1895: 51-55). The qualitative descriptive method is used in this study to clarify the data used and research problems. Data obtained from listening and reading song lyrics, marking slang words, and note taking slang words from Greyson Chance's song lyrics. The results showed that from a total of 19 Greyson Chance songs, 31 types of primary slng words were found. These slang words were created through a blending process, there were 6 slang data, clipping 8 slang data, compounding 2 data, coinage 7 data found, borrowing 1 data, and in acronyms found 1 data. In the most dominant process that create slang words is clipping, which is 8 data. No backformation, conversion, and derivation processes were found in the data.